Intellectual structure and thematic map of entrepreneurship education in higher education: A bibliometric analysis - Mohamad, Mohd Amin; Fauzan (Human Resource Management Academic Research Society, 2024)
The aim of this paper is to present a detailed analysis of the literature on entrepreneurship education in higher education published in international journals from 1988 to 2024, determining the intellectual structure of the field of entrepreneurship education and its maturity as an academic field of study. Design/methodology/approach – Using quantitative methodology for literature study, namely bibliometric analysis, relevant papers were obtained from the Scopus database retrieved on September 13, 2024. A total of 604 papers were identified and studied for bibliometric analysis. BiblioMagika, VOSviewer, Publish or Perish software were used for data analysis. While Open Refine was used for data cleaning. Findings – This study identified a significant increase in scientific investigations of entrepreneurship education in higher education in recent years, along with greater collaboration and international research. It was demonstrated that a few countries dominate the entrepreneurship education research area, such as the United States and China, while institutional and individual research results are more evenly distributed. It was also found that authors or institutions dominate the entrepreneurship education literature. Epistemological orientation shows that the published literature is mostly theoretical and descriptive. Research limitations/implications – The database used only focuses on Scopus. Originality/value – This paper makes important contributions. First, it presents the intellectual structure of entrepreneurship education as a discipline. Second, it determines the current maturity of the field based on its epistemological orientation, concluding that entrepreneurship education is maturing, with theory development followed by empirical testing and validation resulting in increasing consensus on the area of study.